Characterization of Novel Antimalarial Compound ACT-451840: Preclinical Assessment of Activity and Dose-Efficacy Modeling. - Amélie Le Bihan; Ruben de Kanter; Iñigo Angulo-Barturen; Christoph Binkert; Christoph Boss; Reto Brun; Ralf Brunner; Stephan Buchmann; Jeremy Burrows; Koen J Dechering; Michael Delves; Sonja Ewerling; et al. (PLoS Medicine)
Background Artemisinin resistance observed in Southeast Asia threatens the continued use of artemisinin-based combination therapy in endemic countries. Additionally, the diversity of chemical mode of action in the global portfolio of marketed antimalarials is extremely limited. Addressing the urgent need for the development of new antimalarials, a chemical class of potent antimalarial compounds with a novel mode of action was recently identified. Herein, the preclinical characterization of one of these compounds, ACT-451840, conducted in partnership with academic and industrial groups is presented. Method and findings The properties of ACT-451840 are described, including its spectrum of activities against multiple life cycle stages of the human malaria parasite Plasmodium falciparum (asexual and sexual) and Plasmodium vivax (asexual) as well as oral in vivo efficacies in two murine malaria models that permit infection with the human and the rodent parasites P. falciparum and Plasmodium berghei, respectively. In vitro, ACT-451840 showed a 50% inhibition concentration of 0.4 nM (standard deviation [SD]: ± 0.0 nM) against the drug-sensitive P. falciparum NF54 strain. The 90% effective doses in the in vivo efficacy models were 3.7 mg/kg against P. falciparum (95% confidence interval: 3.3-4.9 mg/kg) and 13 mg/kg against P. berghei (95% confidence interval: 11-16 mg/kg). ACT-451840 potently prevented male gamete formation from the gametocyte stage with a 50% inhibition concentration of 5.89 nM (SD: ± 1.80 nM) and dose-dependently blocked oocyst development in the mosquito with a 50% inhibitory concentration of 30 nM (range: 23-39). The compound's preclinical safety profile is presented and is in line with the published results of the first-in-man study in healthy male participants, in whom ACT-451840 was well tolerated. Pharmacokinetic/pharmacodynamic (PK/PD) modeling was applied using efficacy in the murine models (defined either as antimalarial activity or as survival) in relation to area under the concentration versus time curve (AUC), maximum observed plasma concentration (Cmax), and time above a threshold concentration. The determination of the dose-efficacy relationship of ACT-451840 under curative conditions in rodent malaria models allowed prediction of the human efficacious exposure. Conclusion The dual activity of ACT-451840 against asexual and sexual stages of P. falciparum and the activity on P. vivax have the potential to meet the specific profile of a target compound that could replace the fast-acting artemisinin component and harbor additional gametocytocidal activity and, thereby, transmission-blocking properties. The fast parasite reduction ratio (PRR) and gametocytocidal effect of ACT-451840 were recently also confirmed in a clinical proof-of-concept (POC) study.